DIOSCOREA DELTOIDEA WALL. EX GRISEB. A HIGHLY THREATENED HIMALAYAN MEDICINAL PLANT: AN OVERVIEW - L.R. DANGWAL; AMIT SINGH CHAUHAN (International Journal of Pharma and Bio Sciences, 2015)
Dioscorea deltoidea is belongs to family Dioscoreaceae which produce rhizomes or bulbils, having rich medicinal and economic value. Dioscorea deltoidea rhizomes used for the treatment of different diseases such as digestive disorders, sore of throat for struma, diarrhea, irritability, abdominal pain, wounds, burns, anemia, etc. The genus Dioscorea has recently gained much significant reputation as a source of steroidal saponins like diosgenin. These are significant starting material for synthesis of cortisone, which is useful for the treatment of rheumatic arthritis, and the preparation of sex hormones etc. Diosgenin is a precursor for the chemical synthesis of drug like steroids and it have greatly importance in the pharmaceutical industry. Dioscorea deltoidea has also been exploited for its potential role and various chemical component like cortisone and Diosgenin etc. The present paper main aims is to searching the detailed medicinal properties, phytochemical components, pharmacological properties and causes of threatened of Dioscorea deltoidea.